2020
DOI: 10.1111/ina.12694
|View full text |Cite
|
Sign up to set email alerts
|

Construction of a nomogram for predicting the risk of allergic rhinitis among employees of long‐distance bus stations in China

Abstract: Allergic rhinitis (AR) is an IgE-mediated nasal mucosal inflammatory response whose incidence has increased in recent years. AR is characterized by intermittent or persistent symptoms that can lead to a variety of complications. Nasal congestion, sneezing, nasal secretion, swelling of the nasal mucosa, and sinusitis are the main symptoms. AR is considered to be a risk factor for asthma in both children and adults. 1 The current global prevalence of AR is 10%-25%. 2 In recent decades, the prevalence and morbidi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Further investigations to compare the effects of climate change on AR in different seasons might be needed. Previous studies elucidated that a decrease in air humidity may reduce the threshold of nasal mucosa response to an allergic reaction and increase the incidence of AR (41,42), which could explain our findings. Another analysis of respiratory symptom scores of patients with AR from Shanghai showed that both temperature and humidity are negatively correlated with subjective symptom scores, showing that the symptom scores increase by 0.04 points for every 1 • C decrease in temperature or 10% decrease in humidity (25).…”
Section: Discussionsupporting
confidence: 67%
“…Further investigations to compare the effects of climate change on AR in different seasons might be needed. Previous studies elucidated that a decrease in air humidity may reduce the threshold of nasal mucosa response to an allergic reaction and increase the incidence of AR (41,42), which could explain our findings. Another analysis of respiratory symptom scores of patients with AR from Shanghai showed that both temperature and humidity are negatively correlated with subjective symptom scores, showing that the symptom scores increase by 0.04 points for every 1 • C decrease in temperature or 10% decrease in humidity (25).…”
Section: Discussionsupporting
confidence: 67%
“…This study aimed to determine the associations between indoor noise and depressive symptoms, as well as the combined effects on the demographic, socioeconomic, and behavioral characteristics of hotel workers. Based on our previous research on the microenvironment of residential, 49,50 and public places, 51 we conducted this cross‐sectional and on‐site survey of the hotel noise level to investigate the health effects of the hotel noise level on long‐term indoor staff depression. The primary outcomes were: approximately 40.9% of the hotel exceeded the 45 dB limit (A), 19.1% of hotel workers showed mild to severe symptoms of depression, different building characteristics were associated with indoor noise, and the indoor noise level was significantly a positive association with depression scores>2.…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to determine the associations between indoor noise and depressive symptoms, as well as the combined effects on the demographic, socioeconomic, and behavioral characteristics of hotel workers. Based on our previous research on the microenvironment of residential, 49,50 and public places, 51 we conducted this cross-sectional and on-site survey of the hotel noise level to investigate the health effects of the hotel noise level on long-term indoor staff depression. The primary outcomes were: approximately 40.9%…”
Section: Discussionmentioning
confidence: 99%
“…In fact, nomogram has been constructed in prediction of allergic disease. Li et al [50] developed a nomogram with relative humidity, fungi, self-reported allergic rhinitis symptoms, and exposure to smoking for the prediction of incidence of allergic rhinitis. Santos et al [51] constructed nomograms using skin prick, speci c IgE and basophil activation tests to predict the severe reactions and low threshold dose during peanut challenges.…”
Section: Discussionmentioning
confidence: 99%